2015
DOI: 10.1007/s40831-015-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basicity on Electroreduction with Controlled Oxygen Flow of Molten Slag Containing FeO

Abstract: This paper reports on electroreduction with controlled oxygen flow (COF) for extraction of iron along with oxygen by-product from molten slags containing iron oxide at 1723 K. An electrolytic cell with COF was constructed by an iridium wire cathode and a porous platinum anode sintered on a one-end-closed magnesia-stabilized zirconia-based solid electrolyte tube. Effect of basicity of SiO 2 -CaO-Al 2 O 3 -MgO-FeO slag on electroreduction behavior of FeO was investigated by means of the linear sweep and the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Based on the breakthrough of excellent inert anodes, UTE will provide a feasible and convenient technology to directly produce oxygen from abundant lunar soil on the Moon. [123,124] For the industrial application of UTE, a low-carbon process for metal exaction can be designed and would contribute to the achievement of carbon neutrality. [125,126] Importantly, the entire process-ore pretreatment, energy supply, UTE, product collection, tailings utilization, etc.must be designed and optimized considering the cost, circular economy, and carbon footprint.…”
Section: Low-carbon Ironmaking and Steelmakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the breakthrough of excellent inert anodes, UTE will provide a feasible and convenient technology to directly produce oxygen from abundant lunar soil on the Moon. [123,124] For the industrial application of UTE, a low-carbon process for metal exaction can be designed and would contribute to the achievement of carbon neutrality. [125,126] Importantly, the entire process-ore pretreatment, energy supply, UTE, product collection, tailings utilization, etc.must be designed and optimized considering the cost, circular economy, and carbon footprint.…”
Section: Low-carbon Ironmaking and Steelmakingmentioning
confidence: 99%
“…Stable inert anodes with low cost are still the challenge due to the extreme corrosion conditions, such as ultra‐high temperature, and electrochemical and chemical corrosion, etc. Based on the breakthrough of excellent inert anodes, UTE will provide a feasible and convenient technology to directly produce oxygen from abundant lunar soil on the Moon [123, 124] …”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Our work on aluminum production has shown that adding a high-optical basicity oxide (CaO) to the flux significantly improves the stability of the YSZ membrane. Gao et al have also recently reported a correlation between the optical basicity of the molten salts and the pore formation within YSZ membrane [70]. To completely understand the interaction between each molten flux mixture and the YSZ membrane especially in electrolysis mode, it still requires more detailed investigations from both experimental and theoretical perspectives in the future.…”
Section: Challenges and Future Workmentioning
confidence: 99%